â€œINTRA-RACIAL DYNAMICS OF BLACK FACULTY AND BLACK STUDENTS: BARRIERS TO SUCCESS IN THE ACADEMY IN PREDOMINANTLY WHITE INSTITUTIONSâ€ - D. Toliver, Susan; Moore, Penelope J.; Redcross, Natalie (European Scientific Journal, ESJ, 2015)
Intra-racial Black faculty and Black studentsâ€™ communication at predominantly White institutions poses an additional challenge and source of stress for Black faculty. The view of their role vis-Ã -vis Black students is at odds with studentsâ€™ perceptions of Black faculty identity and the Black faculty role impeding Black facultyâ€™s effectiveness as mentors. Black faculty need to address this disconnect in order to increase the academic success of Black students, to decrease Black facultyâ€™s sense of isolation, and to support the interests of their institutions in their attempts to increase Black student retention and multicultural transformation of the academy.